Between 'Religious Denomination' and 'Social Diversity': On the Future of Religious Education in Poland - Mariusz Chrostowski; Urlich Kropač (Nicolaus Copernicus University in Toruń, 2023)
In recent years, Polish society has observed an intensification of changes in socio-religious conditions. In a special way, they have become the 'hallmark' of young Poles, who already exist uniquely between 'religious denomination' and 'social diversity.' The current form of Religious Education (school catechesis) is therefore becoming less and less compatible with the daily life of youth and will thus undoubtedly be difficult to maintain in the future in an unchanged form. In this context, this article - anchored in a critical analysis of the present - is an attempt to 'explore' the future of Religious Education in Polish schools. To begin with, the authors present the symptoms of 'social exhaustion' concerning school catechesis and then focus on presenting 'dialogue' as a religious-pedagogical path of the future. The last paragraph is devoted to conceptual dilemmas, which include not only tasks related to the future teaching of religion, but also present guidelines related to the search for a future model of Religious Education in Poland.